Empowering Communities Through Hydroponic Urban Farming: Skill Development, Business Opportunities, and Green Village Implementation - Silitonga, Riana Magdalena; Kristiana, Stefani Prima Dias; Budiyanta, Nova Eka (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the capacity of the Sampora Village community, Tangerang, in developing sustainable urban farming through the implementation of hydroponic systems. The program addresses the need for alternative agricultural practices in urban areas to support food security and environmental sustainability. The methods employed included educational counseling on sustainable agriculture, hands-on training in basic hydroponic techniques, technical guidance on advanced hydroponic piping systems, and interactive discussions and question-and-answer sessions to strengthen participants’ understanding. Community members were actively involved as participants, while practical learning tools such as hydroponic installation equipment and nutrient management systems were utilized throughout the program. Data were analyzed using a descriptive approach, combining quantitative analysis of pre-test and post-test results. The findings indicate significant improvements in participants’ competencies, including increased understanding of hydroponic systems from 20% to 85%, installation skills from 15% to 80%, nutrient management knowledge from 10% to 78%, and maintenance skills from 12% to 82%. In addition, participants developed awareness of potential business opportunities, such as selling fresh produce to local markets. In conclusion, the implementation of hydroponic-based urban farming had a positive impact on community empowerment, environmental awareness, and local economic development, thereby contributing to the creation of sustainable and resilient urban communities.